A tracable proactive anonymous electronic cash - Chang, Yu Cheng; Seman, Kamaruzzaman; Yunus, Jasmy (2000)
In this paper, we propose a traceable anonymous electronic cash, based on Digital Signature Scheme (DSS), but with difference whereby the coin's anonymity can be revoke by a quorum of the server. Our system, unlike previous anonymous systems, can prevent crimes from successfully being perpetrated, and employs revocation to do so. We introduce this traceable electronic cash that require a quorum of servers to produce a signature to the receiver, and a (possibly different) quorum to be unblended the coin. We also applied the method of bints to our protocol to enable tracing of correctness of the signature, and the corresponding coins.